Redes, relações e subgrupos: uma análise da estrutura relacional das empresas do setor automotivo - Ferreira, Augusto Squarsado (2018)
The research seeks to show and analyze among 20 major automakers in the global automotive industry, how the actors are organized concerning the network topology and how central they are, assessed by the indegree centrality regarding their structural position. Furthermore, two hypotheses will be proposed, and analyzes of similarities will be made through correlations tests between the actors’ both production, revenue and profit performance attributes and indegree centrality values. In order to accomplish this, we collected 1359 relationships of four specific governance structures from 2011, 2012 and 2013 mainly from the Automotive News magazine guide, and we arranged them in edge lists observing particularly the money flow for each arc. The algorithm called the Louvain method identified cohesive subgroups, and the indegree centrality algorithm counted the money flow. The results show a network structure characterized by communities, as well as moderate to strong similarities between the actors and the subgroups formed by them with their respective revenue and the money flow for the three years accounted here.